2022
DOI: 10.1002/jcb.30299
|View full text |Cite
|
Sign up to set email alerts
|

Investigating binding mechanism of thymoquinone to human transferrin, targeting Alzheimer's disease therapy

Abstract: Iron deposition in the central nervous system (CNS) is one of the causes of neurodegenerative diseases. Human transferrin (hTf) acts as an iron carrier present in the blood plasma, preventing it from contributing to redox reactions. Plant compounds and their derivatives are frequently being used in preventing or delaying Alzheimer's disease (AD). Thymoquinone (TQ), a natural product has gained popularity because of its broad therapeutic applications. TQ is one of the significant phytoconstituent of Nigella sat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 103 publications
0
19
0
Order By: Relevance
“…Transferrin (Tf) is a widely used targeting ligand and can selectively bind with the transferrin receptor (TfR) on the cancer cell membrane, suggesting that Tf is a good choice in the application of cell targeted delivery and disease treatment. [45][46][47] Human Tf (hTf, 79 kDa) is a kind of monomeric glycoprotein and the carbohydrate moieties approximately represent 6% of its mass. 48 Based on the cis-diols structure in the sugar chain of glycoproteins, Tf can be covalently conjugated on the benzoboroxole modified nanoparticles in a siteoriented manner by the formation of a five-membered cyclic ester.…”
Section: Study Of the Elution Conditions For Determining The Tf Bindi...mentioning
confidence: 99%
“…Transferrin (Tf) is a widely used targeting ligand and can selectively bind with the transferrin receptor (TfR) on the cancer cell membrane, suggesting that Tf is a good choice in the application of cell targeted delivery and disease treatment. [45][46][47] Human Tf (hTf, 79 kDa) is a kind of monomeric glycoprotein and the carbohydrate moieties approximately represent 6% of its mass. 48 Based on the cis-diols structure in the sugar chain of glycoproteins, Tf can be covalently conjugated on the benzoboroxole modified nanoparticles in a siteoriented manner by the formation of a five-membered cyclic ester.…”
Section: Study Of the Elution Conditions For Determining The Tf Bindi...mentioning
confidence: 99%
“…N. sativa effects on memory have been subject to only a few studies, but existing evidence point out that it would have a positive impact on memory and learning ( Alasmari et al, 2022 ; Kantar et al, 2022 ; Khan et al, 2022 ; Xue et al, 2022 ). In the radial arm maze test of rats, research has shown that both long- and short-term administration of N. sativa oil can improve working memory, especially short-term memory.…”
Section: Black Cumin ( Nigella Sativa (L) [Ranuncu...mentioning
confidence: 99%
“…Naturally occurring compounds have been comprehensively investigated to develop safe and potent inhibitor(s) of MARK4 24,36‐38 . Natural products (NPs) have conventionally been the wealthiest resource of biologically active compounds utilized as therapeutic drugs 34,39‐44 .…”
Section: Introductionmentioning
confidence: 99%